Survey to describe variability in early onset scoliosis cast practices. (August 2018) - Grzywna, A.; McClung, A.; Sanders, J.; Sturm, P.; Karlin, L.; Glotzbecker, M.; Children's Spine Study Group,; Growing Spine Study Group,
Purpose: To investigate paediatric orthopaedists' cast practices for early onset scoliosis regarding patient selection, cast application, radiographic evaluation, treatment cessation and adjunctive bracing. Methods: A casting survey was distributed to all paediatric orthopaedists in Children's Spine and Growing Spine Study Groups (n = 92). Questions included physician and patient characteristics, technique, treatment, outcomes, radiographic measurements and comparison to other treatments. A total of 55 orthopaedists (60%) responded, and descriptive statistics were calculated on the subset who cast (n = 45). Results: A majority of respondents use cast treatment for idiopathic and syndromic scoliosis patients, but not for neuromuscular or congenital scoliosis patients. Major curve angle ranked most important in orthopaedists' decision to commence cast treatment, in comparison with rib-vertebra angle difference or clinical observations. The major curve angle threshold to initiate casting was a median of 30° (20° to 70°), and the minimum patient age was median ten months (3 to 24). First in-cast and out-of-cast radiographs are taken standing, supine, awake, under anesthesia and/or in traction. In all, 58% consistently cast over or under the arm, while 44% vary position by patient. Respondents were divided about the use of a brace after cast treatment: 22% do not prescribe a brace, 31% always do and 36% do in some patients. Conclusions: Future multicentre research studies must standardize radiographic practices and consider age and major curve angle at cast initiation and termination, scoliosis aetiology, shoulder position and treatment duration. Practices need to be aligned or compared in these areas in order to distinguish what makes for the best cast treatment possible. Level of Evidence: V, Expert opinion